2006
DOI: 10.2460/javma.228.11.1718
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of results of computed tomography and radiography with histopathologic findings in tracheobronchial lymph nodes in dogs with primary lung tumors: 14 cases (1999–2002)

Abstract: Results of CT evaluation of TBLN status were in agreement with histopathologic findings and more accurate than use of thoracic radiography for evaluating TBLNs in dogs with primary lung tumors. Computed tomography imaging should be considered as part of the staging process to more accurately assess the TBLNs in dogs with primary lung tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 9 publications
1
66
1
5
Order By: Relevance
“…A possible alternative to methylene blue dye or technetium is thoracic CT imaging; lymphadenopathy as detected with CT imaging has been strongly correlated with metastasis in dogs with primary lung tumors (Ballegeer et al, 2010;Marolf et al, 2011;Paoloni et al, 2006). Future intrathoracic lymph node biopsy recommendations should include description to penetrate the mediastinal pleural envelope and dissect overlying fat to remove any palpable or visual N2 lymph nodes in dogs presenting for resection of primary lung tumors.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A possible alternative to methylene blue dye or technetium is thoracic CT imaging; lymphadenopathy as detected with CT imaging has been strongly correlated with metastasis in dogs with primary lung tumors (Ballegeer et al, 2010;Marolf et al, 2011;Paoloni et al, 2006). Future intrathoracic lymph node biopsy recommendations should include description to penetrate the mediastinal pleural envelope and dissect overlying fat to remove any palpable or visual N2 lymph nodes in dogs presenting for resection of primary lung tumors.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that the prognosis of dogs having metastatic spread of primary lung tumors to regional intrathoracic lymph nodes is poorer than in dogs without lymph node metastasis (McNiel et al, 1997;Ogilvie et al, 1989;Paoloni et al, 2006;Polton et al, 2008;Sabattini et al, 2012). Recommendations have been made that the regional intrathoracic lymph nodes are to be surgically biopsied during a lung tumor resection, but without specific guidance (Fossum, 2007;Laksito et al, 2010;McNiel et al, 1997;Paoloni et al, 2006;Rebhun and Culp, 2013). In some studies of canine lung tumors, tracheobronchial lymph nodes were not biopsied if they appeared to be of normal size, though lymph node size is not indicative nor correlative for metastasis (Lansdowne et al, 2005;McNiel et al, 1997;Paoloni et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Independent from its size, any intra parenchymal hypo attenuation is considered abnormal, and when there is obliteration of fat adjacent to them, this can represent an extra nodal spread from a tumor or postsurgical or post radiotherapy inflammation. Palaoni et al (2006) reported the importance of contrast enhancement of the tracheobronchial lymph node in dogs with diagnosis of a primary lung tumor. They reported that even with minimal lymph node enlargement, when they present significant contrast enhancement, homogeneous or ring like, abnormality should be considered.…”
Section: Introductionmentioning
confidence: 99%